C4b-binding protein as an antigenic target in the pathogenesis of antiphosphatidylethanolamine autoantibodies - Songwang Hou; Paul F. Lindholm; Joshua M. Thurman; Jungwha Lee; Rosalind Ramsey-Goldman; Ming Zhao (Proceedings of the National Academy of Sciences, 2026)
Autoantibodies against phosphatidylethanolamine (PE), a major phospholipid in cell membranes, are associated with symptoms of thrombosis and obstetric complications. A growing body of evidence indicates the involvement of a cofactor for the reactivity of anti-PE (aPE) antibodies. The goals of this study were to identify the putative cofactor and investigate the pathogenic roles of aPE antibodies. Existing ELISA-based assays for detecting aPE antibodies showed that the bovine plasma is a known source of cofactor for the manifestation of reactivity by aPE antibodies. We used affinity pull-down and serial fractionation to purify the cofactor from bovine plasma and identified it as the C4b-binding protein (C4BP), which is a conserved inhibitor in the complement cascade. The human C4BP was subsequently shown to bind PE membrane with specificity and is targeted by aPE antibodies which led to elevated complement activation. Similarly, murine aPE antibodies bind C4BP, hindering its inhibitory function, causing heightened complement activation in vitro and in vivo in a mouse model of renal ischemia and reperfusion, which was antagonized by the coadministration of an anti-C5 antibody. Collectively, the present data identified C4BP with PE-binding specificity and as an antigenic target for aPE antibodies, which cause complement activation. These findings shed light on the pathogenic mechanism of aPE antibodies with implications in diagnosis and therapeutic treatment.